Sleep-Related Cognitive Processes and the Incidence of Insomnia Over Time: Does Anxiety and Depression Impact the Relationship? - Norell-Clarke, Annika; Hagström, Mikael; Jansson-Fröjmark, Markus (Frontiers in Psychology, 2021)
Aim: According to the Cognitive Model of Insomnia, engaging in sleep-related cognitive processes may lead to sleep problems over time. The aim was to examine associations between five sleep-related cognitive processes and the incidence of insomnia, and to investigate if baseline anxiety and depression influence the associations. Methods: 2333 participants completed surveys on nighttime and daytime symptoms, depression, anxiety, and cognitive processes at baseline and six months after the first assessment. Only those without insomnia at baseline were studied. Participants were categorized as having or not having incident insomnia at the next time point. Baseline anxiety and depression were tested as moderators. Results: Three cognitive processes predicted incident insomnia later on. Specifically, more safety behaviors and somatic arousal at Time 1 increased the risk of developing insomnia. When investigating changes in the cognitive processes over time, reporting an increase of worry and safety behaviors also predicted incident insomnia. Depressive symptoms moderated the association between changes in worry and incident insomnia. Conclusion: These findings provide partial support for the hypothesis that cognitive processes are associated with incident insomnia. In particular, safety behaviors, somatic arousal and worry increase the risk for incident insomnia. Preventative interventions and future research are discussed.